AB0429 The association between psychosocial factors and physical activity measured by actigraphy in patient with rheumatoid arthritis. (23rd January 2014) - van Dartel, S.; Repping-Wuts, H.; Knoop, H.; van Hoogmoed, D.; Bleijenberg, G.; van Riel, P.; Fransen, J.
Abstract : Background: Previous studies showed that fatigue in RA is related to pain and disability, and to several psychosocial factors including coping and cognitions. Physical activity patterns, especially a pervasively passive pattern, are related to RA fatigue. Psychosocial factors and specific coping styles may be associated with activity patterns in patients with RA. Objectives: The objective of this study was to investigate whether there is an association between self-efficacy with respect to fatigue, coping style, beliefs about fatigue, and activity patterns in RA patients. Methods: Consecutive RA patients of the rheumatology clinic of the Radboud University Nijmegen Medical Centre (N=152) were enrolled for this study. Patients physical activity during 12 consecutive days was measured with the actometer. A general physical activity score (DOM) reflected the average physical activity over the total 12-day time period and was expressed in the average number of accelerations per 5-min period. The individuals' activity patterns were based on 12 individual daily physical activity scores. Patients with at least 90% of the daily activity scores below the DOM were classified as pervasively passive while the remaining patients were labeled as (pervasively or fluctuating) active. Beliefs regarding the somatic and non-somatic causes of fatigue were assessed using the Causal Attribution List (CAL), consisting of a somatic and non-somatic factor. Self-efficacy concerning fatigue was assessed using the Self-Efficacy Scale 28 (SES28). Coping strategies were assessed using the Modified Fatigue Coping Inventory (MPC-I-F). Catastrophizing of fatigue was assessed with the Fatigue Catastrophizing Scale. The association between these psychosocial factors and active/passive daily activity patterns was analyzed using an independent t-test or Mann-Whitney U test, as appropriate. Results: There were no differences found between causal attributions, self-efficacy, several coping styles and the level of daily activity. Passive patients had resting more frequently as coping style. Conclusions: In RA patients, having a pervasively passive or active activity level was unrelated to beliefs, self-efficacy, and coping style. Therefore, activity level and coping style may be independent factors to target in RA. Disclosure of Interest: None Declared